PENDAMPINGAN DAN STRATEGI PEMBELAJARAN BAGI SISWA ADHD DI SEKOLAH DASAR - Dodik Kurniawan; Adliansyah, Rival Febri; Yulianto Putra, Ega Yudhistira; M. Anas Thohir; Sri Wahyuni; Ahmad Fauzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by difficulties in sustaining attention, impulsive behavior, and hyperactivity, which significantly affects students’ learning processes in school. This study aims to describe the characteristics of students with ADHD, the impact of ADHD on learning, the forms of assistance provided, and the learning strategies implemented to support their academic and social development in elementary school. This research employed a qualitative approach with a descriptive design. Research subjects consisted of classroom teachers, a student with ADHD (referred to as Rehan), and his parents. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings indicate that the student with ADHD experiences difficulties in sustaining attention, following instructions, and regulating behavior, yet demonstrates adequate academic ability in reading, writing, mathematics, and English. ADHD impacts learning by requiring more intensive individualized assistance during classroom activities. Support is provided through collaboration among teachers, parents, and therapists. Effective learning strategies include individualized instruction, direct guidance during task completion, continuous supervision, reinforcement of positive behavior, and the creation of a supportive and low-distraction learning environment. Strong collaboration among schools, families, and professional practitioners is a critical factor in optimizing the academic and social development of students with ADHD in elementary school settings.